Implementation of E-Court in Civil Life Settlement to Realize Simple Principles Quickly and Low Costs (Study in Malang District Court Class 1a) - Ferlyawan Isnanda Nuh; Herwastoeti Herwastoeti; Dwi Ratna Indri Hapsari (Universitas Muhammadiyah Malang, 2022)
The development of technology and information in the digital era as it is today is a significant change in human behavior. The digital era as it is today requires all elements of society and institutions to meet the needs of the community related to the development of this era. On the basis of this fulfillment, the Supreme Court has created an e-court application. This research is a type of empirical legal research. Empirical legal research is oriented to primary data (research results in the field). As for the results of this study, the implementation of e-court at the Malang District Court has been implemented in accordance with Perma No.1 of 2019, there are 4 features of e-court services, namely registration, payment, summons, and trial, all of which are held electronically. This is also an effort made by the Supreme Court to modernize the judicial process in Indonesia without eliminating aspects that existed in the previous judicial system, namely maximizing the existing potential with the support of information and communication technology. In line with the suitability of the simple principle of fast and low cost, the number of cases at the Malang District Court that entered via e-court in 2019 to 2021 reached 4,985 cases, namely civil cases that include applications, lawsuits, simple claims, and objections. In 2019 there were fewer cases that went through compared to cases that went through the manual procedure, but over time the e-court became effective, and manual case registration began to be abandoned. The effectiveness of e-courts in the settlement of civil cases at the Malang District Court has been running effectively since 2020, namely the examination and settlement of issues are carried out in an efficient and effective manner, and at a cost that the community can reach.